2003
DOI: 10.1210/en.2002-0187
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Hyperplasia in a Transgenic Mouse with Prostate-Specific Expression of Prolactin

Abstract: Prolactin (PRL) is one of several polypeptide factors known to exert trophic effects on the prostate. We have previously reported a dramatic prostate enlargement with concurrent chronic hyperprolactinemia and elevated serum androgen levels in a PRL transgenic mouse (Mt-PRL) with ubiquitous expression of the transgene. To address the role of local PRL action in the prostate, a new transgenic mouse model (Pb-PRL) was generated using the prostate-specific rat probasin (Pb) minimal promoter to drive expression of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(123 citation statements)
references
References 52 publications
12
108
0
1
Order By: Relevance
“…Nevertheless, the summarized data provide a generalized view of the implication of the central cytokine signaling in tumor development of [33] and inhibitory role in metastasis progression [45] ). Moreover, it can help us to decipher new mechanisms of activation of the components of the JAK-STAT pathway like receptor and/ or ligand nuclear localization.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the summarized data provide a generalized view of the implication of the central cytokine signaling in tumor development of [33] and inhibitory role in metastasis progression [45] ). Moreover, it can help us to decipher new mechanisms of activation of the components of the JAK-STAT pathway like receptor and/ or ligand nuclear localization.…”
Section: Resultsmentioning
confidence: 99%
“…A constitutively active mutant of JAK2 has been identified in patients with polycythaemia vera [32] . Moreover, increased levels of correspondent ligands can be associated with JAK-STAT induced carcinogenesis: in animal models of prostate and mammary gland hyperplasia with local overexpression of Prl [33,34] ; in humans hyperprolactinemia is considered as a risk factor for breast and, probably, prostate cancer [35,36] ; overexpression of GH in transgenic mice leads to increased frequency of mammary adenocarcinoma [37] . A particular and essential role for neoplasia progression of autocrine production of Prl has been revealed [34,38] .…”
Section: Jak-stat Signaling and Carcinogenesismentioning
confidence: 99%
“…CD24 is a potential oncogene reported to be overexpressed in a large variety of human malignancies. 31 We selected the prolactin receptor for further characterization, as this polypeptide growth factor-receptor axis has been implicated in the development of the normal, 32,33 hyperplastic, 34 and neoplastic 35 prostate. We found the prolactin receptor to be overexpressed in ductal versus acinar adenocarcinoma at both the transcript level and at the protein level, as validated by immunohistochemistry.…”
Section: Discussionmentioning
confidence: 99%
“…We found the prolactin receptor to be overexpressed in ductal versus acinar adenocarcinoma at both the transcript level and at the protein level, as validated by immunohistochemistry. Whether the prolactin receptor might affect ductal adenocarcinoma growth to a greater degree than acinar adenocarcinoma is not known, but it is of interest that prolactin promotes ductal morphogenesis 34 and an increase in volume of ductal epithelium 32 in rodent prostates. It should be noted that the prolactin receptor, although overexpressed in ductal compared with acinar adenocarcinoma, does not seem to be practical marker in immunohistochemistry for ductal adenocarcinoma, because of the overlap in immunopositivity in ductal and acinar adenocarcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the influence of steroid hormones, the action of nonsteroid hormones on the prostate is a potential field of interest, as a relationship between levels of prolactin (PL) and the increase of prostate pathology in men (Bartke, 2004) and rats (Wennbo et al, 1997;Kindblom et al, 2003) has been observed. Moreover, PL stimulates the androgen-independent growth of rat prostate cells in vitro (Ahonen et al, 1999).…”
mentioning
confidence: 99%